Electronic modulation of metal-support interactions improves polypropylene hydrogenolysis over ruthenium catalysts - Kots, Pavel A.; Xie, Tianjun; Vance, Brandon C.; Quinn, Caitlin M.; de Mello, Matheus Dorneles; Boscoboinik, J. Anibal; Wang, Cong; Kumar, Pawan; Stach, Eric A.; Marinkovic, Nebojsa S.; Ma, Lu; Ehrlich, Steven N.; et al. (Nature communications, 2022)
Ruthenium (Ru) is the one of the most promising catalysts for polyolefin hydrogenolysis. Its performance varies widely with the support, but the reasons remain unknown. Here, we introduce a simple synthetic strategy (using ammonia as a modulator) to tune metal-support interactions and apply it to Ru deposited on titania (TiO 2 ). We demonstrate that combining deuterium nuclear magnetic resonance spectroscopy with temperature variation and density functional theory can reveal the complex nature, binding strength, and H amount. H 2 activation occurs heterolytically, leading to a hydride on Ru, an H + on the nearest oxygen, and a partially positively charged Ru. This leads to partial reduction of TiO 2 and high coverages of H for spillover, showcasing a threefold increase in hydrogenolysis rates. This result points to the key role of the surface hydrogen coverage in improving hydrogenolysis catalyst performance. Catalytic pathways of plastic waste valorization to lubricants are attractive avenues to foster circular economy. Tuning of catalyst electronic properties allows to significantly improve its activity due to boosted hydrogen storage on the surface.